The Positive Effect of Population Growth on Agricultural Saving in Irrigation Systems - Simon, Julian L. (The Review of Economics and Statistics, 1975)
Data from a pooled sample of 48 less developed countries on the relationship between population density/acre cultivated land and the proportion of cultivated land that has been irrigated were analyzed to determine the effect of population growth on irrigation investment. The data indicate that population density has a positive effect on the building of irrigation systems. This relationship was somewhat strengthened by the addition of variables such as the cultivated area as a proportion of the total area per capita income geographic dummies and the population density with respect to the countrys entire land area. In addition historical data suggest that population growth stimulates land clearing. An average of 18.4% of cultivated land in the countries analyzed is irrigated indicating a 1% increase in population density would produce a 0.48% increase in the stock of irrigated land. This 0.48% population growth elasticity for irrigation systems contrasts with Leiffs -.56 elasticity of national income savings. Additional research is required to determine the direction of the net effect of population growth on total investment; however it can be assumed that the effect on agricultural investment is positive.